2023
DOI: 10.3390/horticulturae9050555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EC Levels of Nutrient Solution on Glasswort (Salicornia perennis Mill.) Production in Floating System

Abstract: Halophytes have evolved to tolerate high salinity environments. The halophyte glasswort (Salicornia and Sarcocornia species) grows by the sea or in salty soils and can be consumed with pleasure. In this study, the cultivation of glasswort was studied by testing the effects of different electrical conductivity (EC) levels (10, 15, 20, 25, 30 and 35 mS cm−1) of a nutrient solution. Salicornia perennis Mill. was grown on floating systems in unheated greenhouse conditions. To adjust the different EC levels, sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…This implies that those close to the water exhibit higher salinity tolerance. Among the five tested, P. oleracea shows the lowest salt tolerance [42][43][44][45]. Furthermore, our results showed that this species presented the lowest phenolic and flavonoid content, as well as lower antioxidant capacity.…”
Section: Discussionmentioning
confidence: 61%
“…This implies that those close to the water exhibit higher salinity tolerance. Among the five tested, P. oleracea shows the lowest salt tolerance [42][43][44][45]. Furthermore, our results showed that this species presented the lowest phenolic and flavonoid content, as well as lower antioxidant capacity.…”
Section: Discussionmentioning
confidence: 61%
“…A low Na+/K-ratio indicates the plant's resistance to salt stress, as the ability to accumulate K+ in high salinity environments neutralizes the toxicity of Na+ in the cytoplasm [21]. Another important aspect of this ratio is associated with nutrition, as lower values are more suitable for human consumption, as elevated values have been associated with the incidence of hypertension [22]. In our study, we observed a low Na+/K+ ratio indicating the resistance of S. neei to salt stress and its suitability for human consumption.…”
Section: Mineral Composition and Pigmentsmentioning
confidence: 99%